2016
DOI: 10.1039/c4fo01045k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhomogeneity on triglyceride digestion of emulsions using an in vitro digestion model (Tiny TIM)

Abstract: The colloidal behaviour and extent of lipolysis of various emulsions stabilized by whey protein and Tween were studied using the TNO Intestinal Model (TIM) extended with a purposely designed gastric compartment. The in vitro results suggest that creaming of a fatty layer in the gastric region causes a delay in fat entering the small intestinal region, delays and reduces the free fatty acid content in the small intestinal lumen and delays fat absorption. It was shown that controlling the pH with pig gastric jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…This result indicates that neither the presence of alginate, nor the encapsulation of the emulsion in alginate beads affects the homogeneity within the gastric compartment, and thus gastric emptying can be considered homogeneous. This finding differs from results obtained with a tiny-TIM system for dynamic digestion of WPI-stabilized emulsions, showing non-homogeneous emptying (Oosterveld et al, 2016).…”
Section: Lipid Distribution In the Different Compartmentscontrasting
confidence: 99%
See 2 more Smart Citations
“…This result indicates that neither the presence of alginate, nor the encapsulation of the emulsion in alginate beads affects the homogeneity within the gastric compartment, and thus gastric emptying can be considered homogeneous. This finding differs from results obtained with a tiny-TIM system for dynamic digestion of WPI-stabilized emulsions, showing non-homogeneous emptying (Oosterveld et al, 2016).…”
Section: Lipid Distribution In the Different Compartmentscontrasting
confidence: 99%
“…We are aware of the fact that in vivo digestion is even more complex than the system we used, including physiological regulation mechanisms such as back-control, and for example an intestinal mucus layer (Arranz, Corredig, & Guri, 2016), which cannot be included in the DIDGI. So as stated by Oosterveld and co-workers: care must be taken to translate these results to the in vivo reality (Oosterveld et al, 2016), but the great differences found make us hopeful that we have identified an encapsulation method that could induce an ileal brake after ingestion, and that can also be tuned further if needed.…”
Section: Fatty Acid Incorporation In Mixed Micelles In the Intestinalmentioning
confidence: 94%
See 1 more Smart Citation
“…The intragastric behaviour and extent of lipolysis of various emulsions stabilised by different stabilisers was studied. 122,123 For that, the authors used the tiny-TIM with a specifically designed gastric compartment. It consisted of a main body and lower antral part with an L-shape, in contrast to the tubular shape of the TIM-1.…”
Section: Reviewmentioning
confidence: 99%
“…There was a significant increase in MB release in all emulsions resulting from degradation of the interfacial film by the bile salts. 51,71,73,84 Bile extract contains glycodeoxycholic acid, taurodeoxycholic acid, deoxycholic acid, and phospholipids 77 , all of which interact with emulsions. 18,77 Phospholipids, in particular, are known to compete for the oil-water interface, which may have resulted in displacement of interfacial crystals or other surface-active species.…”
Section: Effect Of Environment On Mb Releasementioning
confidence: 99%